The Influence Of Financial Literacy And Future Orientation On Pension Fund Planning Employee Human Capital PT. Bank X - Salmaa RIzki Zumara; Ratna Meisa Dai (International Journal of Management Research and Economics, 2024)
This research aims to determine the influence of financial literacy and future orientation on pension fund planning. This research method used in this study is a quantitative research method with descriptive and verificative research types. The collected data is primary data obtained from the direct distribution of questionnaires to respondents. The population in this study is Human Capital Employee PT Bank X with a sample of 256. The results of the data analysis indicate that financial literacy and future orientation have an impact on pension fund planning, simultaneously and partially. So, the better the financial literacy and future orientation will increase the pension fund planning itself. Suggestions that researchers can give are by improving the financial literacy program, more detailed information on retirement fund planning options to employees, and promoting a positive future orientation.